Fundamentals of legal policy in the field of antimonopoly regulation in the conditions of digitalization of the economy - A. Yu. Sokolov; O. A. Lakaev (Гуманитарные и юридические исследования)
The relevance of this article is determined by its theoretical and practical significance. The theoretical significance of the study of legal policy in the field of antimonopoly activity in the conditions of digitalization of the economy is due to the fact that there is insufficient scientific study of the issues of improving the institute of antimonopoly regulation, taking into account the tendency of economic entities to abuse in the field of competitive relations using new digital technologies; the current state of development of the theory of administrative law shows the formation of the initial stage of research activities aimed at optimizing legal policy in the field of competition protection in the conditions of digitalization of the economy in terms of quantitative and qualitative indicators. The practical significance of this study is due to the fact that the proper scientific justification of the legal policy in the field of competition protection in the context of digital transformation depends on the further development of the norms of the Russian antimonopoly legislation and legislation on administrative responsibility for offenses infringing on the established order of competition, since improving the systematic approach to the development and implementation of this policy can contribute to the introduction of subsequent innovations in the said legislation. This article identifies the main shortcomings of the legal policy in the field of antimonopoly activity in the conditions of digitalization of the economy, due to the emphasis of the subjects of legal policy on the technologies themselves, and not on a systematic approach to its development, which assumes consideration of positive and negative factors of their application and complex interaction of public authorities in this area. The scientific novelty of the article lies in the fact that, based on the analysis of modern legal policy in the field of competition protection in the context of digital transformation, its further prospects are determined, associated with increasing the level of consistency and comprehensive development of its doctrinal foundations, which can contribute to the formation of a regulatory framework corresponding to the challenges of the fourth industrial revolution and stimulate subsequent research in this area.